Konsep Filsafat Retorika Dalam Debat Keagamaan Zakir Naik: Studi Analisis Filsafat Retorika Aristoteles - Asep Saepulah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
In the development of the history of philosophy, both in the West and in the East, Philosophy is not only understood as a tool for thinking alone, but philosophy has become a tool for arguing by compiling a good sentence and delivered it orally which is called the science of rhetoric. Zakir Naik, who is an expert in debating religious discourse, is demanded to be able to rhetoric well. From the results of the study the authors concluded that; First, the philosophy of rhetoric is a part of philosophy that analyzes the composition of a discourse both oral and written which is based on a neatly arranged knowledge in influencing people through the rules of effectiveness and beauty of language. Second, Zakir Naik in rhetoric use the concepts of ethos, pathos, and logos, by paying attention to the beauty of language.